Carinobolus gen. nov. and Costabolus gen. nov., two new, remarkably crested, monospecific genera of spirobolidan millipedes from West Africa, with the proposal of a new tribe, Amblybolini tribus nova (Diplopoda, Spirobolida, Pachybolidae) - Golovatch, Sergei; Vandenspiegel, Didier (Zootaxa, 2022)
Two new genera, Carinobolus gen. nov. and Costabolus gen. nov., both belonging to the very large, widespread, pantropical family Pachybolidae, are described based on Carinobolus complex sp. nov. and Costabolus baculus sp. nov., respectively. Chiefly based on the posterior gonopod being distinctly articulated at midlength, both new genera seem to be especially similar to Amblybolus Keeton, 1964a (three species in western Africa) and Atlanticobolus Hoffman, 1979 (one species from an island off the Brazilian coast), all of them meriting a separate tribal category, Amblybolini tribus nova. A key is proposed to distinguish all four presently accepted genera of the new tribe. The new genera and species are clearly distinguished in showing unusually strongly crested/ribbed metazonae, a character that is only very seldom observed in Pachybolidae generally, and apparently unique among Afrotropical members. Being rather similar in many respects, both new genera and species differ from each other sufficiently well in gonopodal and leg structure, even though both come from forests in southeastern Nigeria close to the border to Cameroon.